Heteroatom-doped reduced graphene oxide integrated with nickel-cobalt phosphide for high-performance asymmetric hybrid supercapacitors. (June 2022) - Javed, U.; Dhakal, G.; Rabie, A.M.; Iqbal, S.; Lee, Y.R.; Lee, J.; Shim, J.-J.
Abstract: The increasing energy demand and lack of sustainable energy storage systems have attracted considerable attention towards electrochemical capacitors. Transition metal phosphides have emerged as excellent electrode materials for electrochemical capacitors because of their highly metalloid characteristics and low cost. This paper reports the synthesis of binder-free nickel-cobalt phosphide nano horns wrapped with phosphorus-doped reduced graphene oxide by a hydrothermal reaction followed by phosphorization. The nickel-cobalt phosphide nano horns are formed by the Kirkendall effect due to differences in the diffusion rates of phosphorus ions and metal sources. The as-prepared electrode delivers a high specific capacity of 264.9 mAh g −1 (2384 F g −1 ) at 1 A g −1 and a high rate capability of 72 % at 15 A g −1 . The asymmetric hybrid supercapacitor consisted of nickel-cobalt phosphide wrapped with phosphorus-doped reduced graphene as the anode, and activated carbon as the cathode yields a good energy density of 39.7 Wh kg −1 and a high power-density of 8.82 kW kg −1 with high cycling stability of 90 % after 10, 000 charge–discharge cycles. The excellent pseudocapacitive properties of the as-prepared binary metal phosphide confirms its value for widespread practical applications in electrochemical supercapacitors. Graphical abstract: Image 1 Highlights: NiCoP@P-rGO hollow nanohorns was synthesized by one-step phosphorization. Binder-free NiCoP@P-rGO/NF electrode exhibits remarkable supercapacitor performance. NCP@P-rGO/NF//AC ASC device delivered excellent energy density and power density.